ANALISIS PERBEDAAN PERSEPSI KONSUMEN PRIA DAN WANITA DALAM MENGKONSUMSI KOPI MERK LUWAK WHITE KOFFIE DI SAMARINDA - -, Rikardo Harefa (EKONOMIA, 2015)
Coffee is one of the brands of coffee that has the largest market share in Indonesia, this is because the quality of the products of the brand LUWAK WHITE KOFFIE no doubt, as is typical flavor, distinctive aroma, distinctive color, attractive packaging, the price is high.WHITE KOFFIE Luwak coffee is the development of ABC Moca more intended for men, but not the least of women consuming WHITE KOFFIE Luwak coffee. As an illustration, until april 2014 has sold 200,000 cartons LUWAK WHITE KOFFIE, where 150,000 diantarannya purchased by consumers to be male, while another 50,000 purchased by female sex. The purpose of this study to determine the public perception of LUWAK WHITE KOFFIE in Samarinda seen from the typical flavor, distinctive aroma, distinctive color, attractive packaging, high prices and to determine differences in consumer perception of men and women seen from the typical flavor, distinctive aroma , distinctive color, attractive packaging, the price is high.Basic marketing management theory used especially consumer perception by using arithmetic mean and Chi- square analysisBased on the analysis and discussion, the conclusions of this study are:The average value of all indicators count> 3, proving that consumer perceptionsagainst LUWAK WHITE KOFFIE is good, so the hypothesis is assumed that the public perception of LUWAK WHITE KOFFIE in Samarinda seen from the typical flavor, distinctive aroma, distinctive color, attractive packaging, high selling price is pretty good, acceptableOverall it can be concluded that there is no difference between male and female perceptions of the mongoose WHITE KOFFIE in Samarinda, it is supported by sales data in April 2014 has sold 200,000 cartons LUWAK WHITE KOFFIE, where 150,000 cartons diantarannya purchased by the male while 50,000 cartons purchased by female sex. Thus the hypothesis alleged also that there is a difference in perception between men and women seen from the typical flavor, distinctive aroma, distinctive color, attractive packaging, a high selling price,accepted